Vibration Reduction of Layered Sandbags under Traffic Load - Shen, Chenli; Ding, Guangya; Lai, Xiaowei (Geotechnical and geological engineering, 2021)
In this study, a new type of traffic load test device was adopted to investigate the vibration isolation of layered sandbags under train load. The upper part of this device is composed of five high performance hydraulic actuators, to simulate the traffic load produced by train movement. First, sandbags were stacked on the subgrade, which were used as an active vibration isolation barrier. The variations of the soil stress, acceleration and vertical deformation of the sandbag subgrade were analysed by simulating different train speeds, and the relationship between the surface acceleration and train load was established. The attenuation of surface acceleration with depth was further analysed. Then, expanded polystyrene (EPS) foam plates with different thicknesses (placed at a certain distance from the subgrade) were used as a passive vibration isolation barrier. The vibration isolation effect of the EPS foam plate was also analysed. Results show that the sandbag layer used as a subgrade exhibited good vibration isolation effect. At a train load of 15 kN, the acceleration at a depth of 25 cm is less than that at the roadbed surface. The faster the train speed, the higher the acceleration attenuation rate.